Impact of tofacitinib on patient outcomes in rheumatoid arthritis – review of clinical studies - Boyce EG; Vyas D; Rogan EL; Valle-Oseguera CS; O’Dell KM (Patient Related Outcome Measures, 2016)
Eric G Boyce, Deepti Vyas, Edward L Rogan, Cynthia S Valle-Oseguera, Kate M O'Dell Department of Pharmacy Practice, Thomas J Long School of Pharmacy and Health Sciences, University of the Pacific, Stockton, CA, USAAbstract: Rheumatoid arthritis is a chronic, progressive autoimmune disease associated with inflammation and destruction of joints and systemic effects, which result in significant impact on patient's quality of life and function. Tofacitinib was approved for the treatment of rheumatoid arthritis in the USA in 2012 and subsequently in other countries, but not by the European Medicines Agency. The goal of this review was to evaluate the impact of tofacitinib on patient-reported and patient-specific outcomes from prior clinical studies, focusing on quality of life, functionality, pain, global disease assessment, major adverse consequences, and withdrawals. A total of 13 reports representing 11 clinical studies on tofacitinib in rheumatoid arthritis were identified through PubMed and reference lists in meta-analyses and other reviews. Data on improvements in patient-driven composite tools to measure disease activity in rheumatoid arthritis, such as the Health Assessment Questionnaire, served as a major outcome evaluated in this review and were extracted from each study. Additional data extracted from those clinical studies included patient assessment of pain (using a 0–100 mm visual analog scale), patient global assessment of disease (using a 0–100 mm visual analog scale), patient withdrawals, withdrawals due to adverse effects or lack of effect, and risk of serious adverse effects, serious infections, and deaths. Tofacitinib 5 mg bid appears to have a favorable impact on patient outcomes related to efficacy and safety when compared with baseline values and with comparator disease-modifying antirheumatic drugs and placebo. Improvements were seen in the composite and individual measures of disease activity. Serious adverse effects, other adverse consequences, overall withdrawals, and withdrawals due to adverse effects and lack of efficacy are similar or more favorable for tofacitinib versus comparator disease-modifying antirheumatic drugs and placebo. At this point, tofacitinib appears to have an important role in the treatment of rheumatoid arthritis through improvement in these patient outcomes. However, it may require years of additional clinical studies and postmarketing surveillance to fully characterize the benefit-to-risk ratio of tofacitinib in a larger and diverse patient population.Keywords: tofacitinib, rheumatoid arthritis, patient-reported outcomes, quality of life